Soliton Solution of the Nonlinear Time Fractional Equations: Comprehensive Methods to Solve Physical Models - O'Regan, Donal; Aderyani, Safoura Rezaei; Saadati, Reza; İnç, Mustafa (Mdpi, 2024)
In this paper, we apply two different methods, namely, the G/G '-expansion method and the G ' G2 sense and the symmetric regularized long wave equation in the conformable sense. The mentioned nonlinear partial differential equations (NPDEs) arise in diverse physical applications such as ion sound waves in plasma and waves on shallow water surfaces. There exist multiple wave solutions to many NPDEs and researchers are interested in analytical approaches to obtain these multiple wave solutions. The multi-exp-function method (MEFM) formulates a solution algorithm for calculating multiple wave solutions to NPDEs and at the end of paper, we apply the MEFM for calculating multiple wave solutions to the (2 + 1)-dimensional equation. -expansion method to investigate the nonlinear time fractional Harry Dym equation in the Caputo
Keywords: Harry Dym equation; SRLW equation; multi-exp-function method; G/G '--expansion method; G'G2-expansion method